Outcome of Kangaroo Mother Care and Conventional Method of Care - Usman, Anila; Nawaz, Rab; Fatima, Saher; Rehman, Anjum; ., Rumaisa; ., Shumaila (Biological and Clinical Sciences Research Journal, 2025)
The care provided to newborns, particularly preterm, low-birth-weight (LBW), and medically fragile infants, is a critical aspect of neonatal healthcare. Objective: The primary purpose of the study is to find the outcome of kangaroo mother care and conventional care methods. Methods: This randomised control trial was conducted at the Paediatric Department of Lyari General Hospital Karachi from September 2024 to February 2025. A total of 60 patients were included in the study, with 30 infants in each group—one group receiving Kangaroo Mother Care and the other receiving conventional care methods. Infants who were born preterm (before 37 weeks of gestation) or had low birth weight (less than 2500 grams) were included in the study. Infants with major congenital anomalies or those requiring surgical interventions were excluded. Results: Data were collected from 60 participants. There were no significant differences between the two groups across various characteristics: gender (15/15 male/female in KMC vs 16/14 in Conventional Care, p=0.87), mean gestational age (32.5 ± 2.1 weeks in KMC vs 32.3 ± 2.3 weeks in Conventional Care, p=0.78), mean birth weight (1800 ± 300 grams in KMC vs 1750 ± 350 grams in Conventional Care, p=0.65), age at enrollment (12 ± 4 hours in KMC vs 12 ± 5 hours in Conventional Care, p=0.96), maternal age (28.5 ± 4.2 years in KMC vs 29.2 ± 4.5 years in Conventional Care, p=0.56), mode of delivery (18/12 C-section/vaginal in KMC vs. 17/13 in Conventional Care, p=0.80), APGAR score at 5 minutes (7.2 ± 1.1 in KMC vs. 7.4 ± 1.2 in Conventional Care, p=0.42), and maternal health conditions (2 (6.7%) in KMC vs. 3 (10%) in Conventional Care, p=0.73). Conclusion: It is concluded that Kangaroo Mother Care (KMC) offers significant benefits over conventional neonatal care for preterm and low-birth-weight infants, including improved weight gain, better thermoregulation, reduced infection rates, and enhanced breastfeeding success.